Robotic colorectal surgery in Latin America: a systematic review on surgical outcomes - Alves Martins, Bruno Augusto; Avellaneda, Nicolas; Piozzi, Guglielmo Niccolò (Frontiers in Surgery, 2024)
Background and objectivesRobotic approach in colorectal surgery is rapidly gaining interest, particularly in the context of rectal cancer resection. Despite economic barriers, substantial proliferation of robotic colorectal procedures has been observed throughout Latin America. However, there is a lack of data regarding intraoperative and early postoperative outcomes, as well as oncological and long-term results. This systematic review aims to provide an overview of the surgical outcomes of robotic-assisted colorectal approaches across Latin America.Material and methodsA systematic literature search of electronic databases, including PubMed, LILACS, Scopus, Cochrane Library and Scielo, was performed and reported in line with Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. The main target of the literature search was studies that reported outcomes of colorectal robotic surgery in Latin America.ResultsA total of 9,694 published articles were identified from the initial search. Nine thousand six hundred thirty-six publications were excluded after title and abstract review and removal of duplicates. Fifty-eight articles were thoroughly reviewed, and 11 studies met the inclusion criteria. The critical appraisal of study quality (biases risk assessment) was performed according to the Joanna Briggs Institute (JBI) Manual for Evidence Synthesis. In general, the overall study quality was poor. Of the 11 studies included in the analysis, ten addressed intraoperative and early postoperative outcomes, seven addressed oncological/pathological outcomes, and just one addressed long-term outcomes. Ten studies evaluated intraoperative and early postoperative outcomes, encompassing a total of 425 patients, the majority of whom were diagnosed with colorectal cancer. Morbidity rates exhibited a range between 0% and 45.9%, while mortality ranged from 0% to 2.5%.ConclusionFew studies have been published addressing intraoperative, postoperative, pathological, and oncological outcomes of robotic colorectal surgery in this region. Undoubtedly, there are unique challenges not encountered by developed countries, including economic obstacles in establishing structured training programmes and high-quality centres for the development of robotic surgery. Further studies are needed to assess the real extent of robotic surgery in the region and its results.Systematic Review Registrationhttps://www.crd.york.ac.uk/, PROSPERO (CRD42023494112).